PENGEMBANGAN MEDIA POWERPOINT BERBASIS GEOGEBRA PADA POKOK BAHASAN TEOREMA PYTHAGORAS - Edy Nurfalah; Nur Safinah (Jurnal Riset Pembelajaran Matematika, 2021)
This research aims to identify the validity of the development of GeoGebra-based Power Point learning media on the subject of the Pythagorean theorem for junior high school students. This research procedure uses research and development. The development model used is the Thiagarajan 4-D development model which is divided into 4 sessions, namely the Definition session, the Design session, the Development session, and the Disseminate session. In this research, the dissemination session could not be attempted due to research limitations, namely the COVID-19 pandemic. The information collection instrument was in the form of module expert validation sheets and media experts. Information analysis method uses quantitative descriptive. In the results of the information analysis, the average validity or feasibility score of the material was 84, 44% in the very good category and the average media validity or feasibility score was 86, 90% in the very good category. It is concluded that the results of the validation test of GeoGebra-based PowerPoint learning media on the subject of the Pythagorean theorem for junior high school students are very good for use in learning at school.